2019
DOI: 10.15171/ipp.2020.10
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effect of including omega-3 to treatment regimen in elderly patients with ulcerative colitis with placebo: A randomized clinical tria

Abstract: Introduction: Ulcerative colitis is a chronic inflammatory disease which reduces the quality of life and patients’ productivity. People in different ages could be affected since its complications such as colon perforation and cancer are common. Oxidative stress is reported to create an imbalance between reactive oxygen species (ROS) and antioxidant defense systems which occurs in inflammatory tissues and predisposing malignant tumors. Objectives: We aimed to evaluate the effects of omega-3 on inflammatory, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…In this systematic review with meta-analysis, a total of 19 studies were identified according to the predefined inclusion criteria (Figure 1). Among them, 9 studies (47.3%) focused solely on patients with UC [11][12][13][14][15][16][17][18][19], 6 studies (31.6%) included only patients with DC [20][21][22][23][24][25], and 4 studies (21.0%) encompassed both diseases (CD and UC) [26][27][28][29]. Most of the studies (n = 17; 89.5%) involved adult patients, while 2 studies (11.5%) were specifically conducted on children and adolescents [24,25].…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this systematic review with meta-analysis, a total of 19 studies were identified according to the predefined inclusion criteria (Figure 1). Among them, 9 studies (47.3%) focused solely on patients with UC [11][12][13][14][15][16][17][18][19], 6 studies (31.6%) included only patients with DC [20][21][22][23][24][25], and 4 studies (21.0%) encompassed both diseases (CD and UC) [26][27][28][29]. Most of the studies (n = 17; 89.5%) involved adult patients, while 2 studies (11.5%) were specifically conducted on children and adolescents [24,25].…”
Section: Search Resultsmentioning
confidence: 99%
“…Most of the studies (n = 17; 89.5%) involved adult patients, while 2 studies (11.5%) were specifically conducted on children and adolescents [24,25]. The selected studies exhibited diverse designs, with 15 studies (78.9%) being double-blind, placebo-controlled randomized trials [11,12,[14][15][16][17][18][19][20][21][22][23][26][27][28].…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, antioxidants such as marine oil omega-3 can downregulate the inducible isoforms of nitric oxide, myeloperoxidase, lipoxygenases, cyclooxygenase, and nicotinamide adenine dinucleotide phosphate oxidase. They can also prevent the formation of free radicals by enhancing glutathione peroxidase, catalase, superoxide dismutase, paraoxonase, and peroxiredoxins (46,47,53).…”
Section: Radical Scavenging Effectmentioning
confidence: 99%